Numerical Study on the Seismic Behaviour of Aggregate Reinforced Concrete Block Masonry Buildings - Saavedra-Flores, E; Torres-Olivares, S (SPRINGER, 2025)
Current seismic codes predominantly focus on isolated structures, despite the widespread presence of building aggregates in urban environments. This issue is particularly relevant in Costa Rica, where partially grouted reinforced concrete block masonry (PG-RCM) buildings are routinely constructed directly adjacent to each other with no separation, forming aggregates through contact between independent walls rather than shared structural elements. These modern aggregate configurations, frequently built on varying ground elevations, represent a common construction practice whose complex seismic interactions are not explicitly addressed in typical design provisions. This study investigates the seismic behaviour of contemporary PG-RCM aggregates through advanced numerical modelling. The research employs non-linear dynamic analysis with bidirectional seismic excitation, using multilayered shell elements with integrated reinforcement and a damage-based material model for masonry components. The numerical model was validated against experimental data from cyclic pseudostatic loading test on individual PG-RCM wall panel. Subsequent analyses examined both isolated and aggregate configurations, with compression-only contact interactions between adjacent units modelled through zero-length elements. A five-unit aggregate model proved sufficient to capture the effects of structural interactions. The results reveal that in level-ground arrangements, damage concentrates in one end unit of the aggregate, which acts as an energy dissipator through contact-based load transfer, thereby reducing damage in adjacent units. When units are built at different elevations, a critical height difference threshold was identified, above which the highest unit consistently experiences the most severe damage, regardless of its position in the aggregate. These findings demonstrate how contact interaction between adjacent structures significantly alters their seismic response, particularly when combined with elevation differences, emphasising that these complex interactions warrant further investigation to inform the potential future development of targeted seismic design guidance.